Out of the shadows : women in Malay court narratives - Ruzy Suliza Hashim, author 281356 (Bangi : Penerbit UKM, 2003)
This book highlights the problematics of the notion that marginal positioning of women in selected Malay court narratives equates with their apparent insignificance in the history of Malay kings. The women are classified into three groupings: they are silent, consenting or dissenting women, and either individually and collectively, they unsettle the patriarchal principles which govern their lives. By looking through the lenses of feminist dialogics, social exchange, and Islamic theology – at times singly, and at other times in combination – it is argued that women were in fact central in the lives and tribulations of Malay kings.